My partner looks like an animal. Sociological readings on the act of nicknames in the school environment - De los Ángeles Sulca, Elisa Martina (2024)
This article proposes a series of reflections on the socio-subjective effects of the act of nicknames in the fabric of school interaction. Particularly, it analyzes a series of disparaging terms used by indigenous youth such as “choscha”, “quirca” and “loro barranquero”; those that refer to a comparison between people and traits of animals native to their community. The metaphor of animality present in student adjectives can be interpreted as an expression of racism as it operates as an unconscious mechanism that reproduces naturalized beliefs of superiority (human) and inferiority (animal). Nicknames constitute a form of symbolic violence that configure experiences and images of self-hatred.